2019
DOI: 10.1080/2162402x.2019.1629257
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant fucosylation enables breast cancer clusterin to interact with dendritic cell-specific ICAM-grabbing non-integrin (DC-SIGN)

Abstract: Clusterin is a glycoprotein able to mediate different physiological functions such as control of complement activation, promotion of unfolded protein clearance and modulation of cell survival. Clusterin is overexpressed in many types of cancers and a large body of evidence suggests that it promotes carcinogenesis and tumor progression. We have previously described a novel clusterin glycoform present in human semen, but not in serum, highly enriched in terminal fucose motifs. Here we show that human luminal bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The former one formed α-1,6-fucosylation, the main type of N-fucosylation which is under the charge of fucosyltransferases 8 (Fut8) transferring GDP-L-fucose to GlcNAc residue 35 . The latter one formed α-1,2-fucosylation or α-1,3/4-fucosylation which is under the charge of Fut1-2 or Fut3-7/9-11 transferring GDP-L-fucose to terminal galactose or acetyl glucosamine residue 36 . Moreover, core fucosylation and α-1,2-fucosylation can be specifically bound and recognized by LCA and UEA-I lectin respectively 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The former one formed α-1,6-fucosylation, the main type of N-fucosylation which is under the charge of fucosyltransferases 8 (Fut8) transferring GDP-L-fucose to GlcNAc residue 35 . The latter one formed α-1,2-fucosylation or α-1,3/4-fucosylation which is under the charge of Fut1-2 or Fut3-7/9-11 transferring GDP-L-fucose to terminal galactose or acetyl glucosamine residue 36 . Moreover, core fucosylation and α-1,2-fucosylation can be specifically bound and recognized by LCA and UEA-I lectin respectively 37 .…”
Section: Discussionmentioning
confidence: 99%
“…An additional example of relevant lectins of the immune system is the dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN), which is present in macrophages. The interaction between this lectin and fucosylated glycans promotes tumor evasion from the immune response in breast cancer [ 64 ].…”
Section: The Impact Of Glycosylation In Cancer Progressionmentioning
confidence: 99%
“…Other abnormal glycans expressed by BC cells have been reported to modulate macrophages [ 37 , 46 ]. Merlotti et al reported an increase in fucosylated clusterins with terminal sialylation in BC tissues [ 77 ]. Clusterins are highly glycosylated glycoproteins, being one of the most prominent extracellular chaperones, involved in scavenging and clearance events [ 78 ].…”
Section: Tumour-associated Macrophages Recognise Altered Glycosylamentioning
confidence: 99%